1944
DOI: 10.1084/jem.79.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Isolation From Normal Mice of a Pneumotropic Virus Which Forms Elementary Bodies

Abstract: In the course of attempts to isolate viruses by direct inoculation of albino Swiss mice with throat washings from clinical cases of influenza, non-influenzal pneumonias were frequently encountered in the passage mice. The pneumonias observed were of two types. One type was indistinguishable in the gross from that produced by influenza virus and the etiological agent of this type was found to be a filterable virus which was subsequently identified, on the basis of serological reactions, with that described by H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

1946
1946
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…These studies employed the natural mouse pathogen C. muridarum, which was originally isolated from a mouse with respiratory infection (33,34). The time course, as well as the immunological and histopathological progression, of C. muridarum infection of mice closely resembles that observed with Chlamydophila pneumoniae infection in humans (8, 9).…”
Section: Discussionmentioning
confidence: 99%
“…These studies employed the natural mouse pathogen C. muridarum, which was originally isolated from a mouse with respiratory infection (33,34). The time course, as well as the immunological and histopathological progression, of C. muridarum infection of mice closely resembles that observed with Chlamydophila pneumoniae infection in humans (8, 9).…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively little can yet be gleaned from genome comparisons on differential pathogenic properties of chlamydiae. Five of the six fully sequenced genomes are from chlamydiae infecting humans, with the remaining one being from the mouse biovar of C. trachomatis (MoPn), which was initially isolated from lungs of serially passaged mice inoculated with throat washings from clinical cases of human influenza (Nigg & Eaton, 1944). Moreover, only limited consideration of the evolutionary path of Chlamydia has been possible to date as the genome sample size is still too small (C. trachomatis and C. pneumoniae).…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…This virus was recognized first in 1938 in New York during the course of studies with Swiss mice. It has been encountered since in similar mice in California (3) and Minnesota (4). Further investigations carried out in this laboratory revealed that pneumonia virus of mice could be obtained from numerous different stocks of mice, and that latent infection by it was not confined solely to Swiss mice.…”
mentioning
confidence: 96%